2020
DOI: 10.1111/jen.12744
|View full text |Cite
|
Sign up to set email alerts
|

Electroantennogram responses of Plutella xylostella (L.), to sex pheromone components and host plant volatile semiochemicals

Abstract: The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is a notorious insect pest of cruciferous crops worldwide. Attract‐and‐kill strategies to manage the DBM based on insect pheromone and plant volatile semiochemicals have been explored and partially applied in the field. However, little is known about whether the attractant effects of insect pheromone and host plant volatile semiochemicals on insects are affected by insect age or volatile concentrations. Therefore, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…4 Previous research showed that both males and females of P. xylostella can detect a broad range of plant volatiles, but only males respond to female sex pheromone components. 25 Taken together with our results, it is reasonable to speculate two olfactory mechanisms for the cross-species inhibition. The first is that the olfactory receptors in male P. xylostella antennae that respond to the three heterospecific pheromone components are also broadly tuned to a range of moth pheromone components.…”
Section: Discussionsupporting
confidence: 81%
“…4 Previous research showed that both males and females of P. xylostella can detect a broad range of plant volatiles, but only males respond to female sex pheromone components. 25 Taken together with our results, it is reasonable to speculate two olfactory mechanisms for the cross-species inhibition. The first is that the olfactory receptors in male P. xylostella antennae that respond to the three heterospecific pheromone components are also broadly tuned to a range of moth pheromone components.…”
Section: Discussionsupporting
confidence: 81%
“…The sensitivity of DBM females to the five active compounds or two blends was assessed through the EAG method as described by Wu et al with slight modifications . Blend-1 was a mixture of equal amounts of the five bioactive compounds, and blend-2 was a five-component mixture (1:5:3:4:3) that mimics the volatile bouquet from geranium.…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of DBM females to the five active compounds or two blends was assessed through the EAG method as described by Wu et al with slight modifications. 30 Blend-1 was a mixture of equal amounts of the five bioactive compounds, and blend-2 was a five-component mixture (1:5:3:4:3) that mimics the volatile bouquet from geranium. Each test chemical at three concentrations (1, 10, and 100 μg/μL) was applied to a single antennal preparation and tested from low to high concentrations, with 10 μL of paraffin oil as a control.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…It is common that electroantennogram (EAG) responses to sex pheromone components are stronger in males than in females but weaker to host volatiles. In P. xylostella , the response of males to sex pheromone constituents is higher than to host plant odorants, but females have a higher EAG response to plant odorants than to sex pheromones ( Palaniswamy et al 1986 , Pivnick et al 1994 , Wu et al 2020 ). Therefore, it is reasonable to speculate that Pxyl CSP11 may be sensitive to the sex pheromone besides plant volatiles in the olfactory communication.…”
Section: Discussionmentioning
confidence: 99%